Spatiotemporal dynamics of soil moisture and matric potential under different land covers at an agricultural site - Dongdong Wu; Tiejun Wang; Yibin Dai; Zhang Yu; Jing Xu (Agricultural Water Management)
Knowledge of the spatiotemporal patterns of soil moisture content (θ) and soil matric potential (ψ) is important for understanding landscape hydrological processes and agricultural management. Previous studies mostly focused on θ, while relevant studies on the spatiotemporal characteristics of ψ were still limited. In this study, the spatiotemporal patterns of θ and ψ were jointly investigated by one-year θ and ψ data, which were collected at 30 cm and 60 cm along a 100-m transect under cropped conditions and a 20-m transect under bare surface conditions in the North China Plain. The results showed that the spatial mean-variance relationship for both θ and ψ displayed upward convex relationships, and vegetation tended to reduce the spatial variability in θ and ψ through root water uptake processes, particularly at deeper soil layers (60 cm), suggesting that the spatial variability in θ and ψ at field scales depended on both moisture and land cover conditions. Moreover, the temporal stability analysis (TSA) revealed that the temporal stability of θ and ψ was different at the study site, which attributed to the influence of vegetation. The correlations between soil texture and the mean relative differences of θ and ψ further confirmed the effect of vegetation at field scales. Due to the different spatial patterns of θ and ψ, the representative sites for monitoring areal average θ and ψ differed, although the results demonstrated the usefulness of the TSA for selecting representative sites for both θ and ψ. Finally, the wavelet coherency analysis was employed to examine the spatial patterns of θ and ψ under cropped conditions. The results revealed that the intra-seasonal spatial stability of θ and ψ was strongly influenced by their large-scale (>8 m) correlations, which were more significant at 30 cm in spring and at 60 cm in summer. This study underscores the necessity to jointly investigate the interactions of θ and ψ with surrounding environments and provided insight into their spatiotemporal variations at field scales.